Consequences of holocaust on physical health of survivors: Bibliography review - Horáčková, Kateřina; Ševčovičová, Andrea; Hrstka, Zdeněk; Moravcová, Markéta; Lásková, Martina; Derňarová, Lubica (My University, 2020)
Objective: Period of elderly age preordains the occurrence of many health issues. People deported during World War II to concentration camps suffered from malnutrition, lack of sleep, physical and mental exhaustion. Recently, the health condition of Holocaust survivors is often complicated as a result of physical punishments and different torture methods as well as mental hardships which they had suffered during deportation. The consequences often have psychosomatic nature thus the survivors are often receivers of health care. The topic of bibliography review is based on the need to objectivize and systematically evaluate subjective health issues of Holocaust survivors in connection with trauma related to the stay in a concentration camp. The aim is to offer a review of effects of the Holocaust on health of different body systems for survivors in concentration camps and Jewish ghettos in the course of World War II. Methods: To map the subjective problems of Holocaust survivors, evidence-based medicine (EBM) method has been used with the help of scientific database PubMed, CINAHL Plus with full text, ProQuest and other sources with specific key words and Boole operators. Prognostic type of clinical/review questions has been selected for the bibliography review, which is trying to predict the probability of relation or output of illness/ condition and based on diseases or symptoms seriousness to find out expectancy for treatment/improvement of care. Results: 175 studies have been found in basic search with the use of key words both in English and in Czech language. The search has not been time-limited. The advanced search has focused on different body systems and health damage due to Nazi experiments. Fourteen studies have been used to complete the study. The research results have confirmed the significant effect of Holocaust trauma on body condition of the survivors. The reasons of this condition were insufficient nutrition, unsuitable and harmful hygienic, living and working conditions and brutality of the guards. According to the research, these factors have impacted all organ systems, mainly locomotion and cardiovascular ones. The results have shown a more frequent occurrence of osteoporosis, fractures of long bones and corresponding chronical pain of people of Jewish origin who had gone through different forms of torture during World War II. Other present symptoms include gastrointestinal problems, tumors mainly in the area of colorectum and lungs. Moreover, the stay in concentration camps had influence on women’s menstrual cycle. Conclusion: The studies of Holocaust effects are an example of the influence of an extreme mental and physical burden on the body condition of the survivors’ health. The results of the studies have shown a wide range of the effects also in mental and social areas.
Dopady holokaustu na tělesnou oblast zdraví - literární rešerše
Keywords: concentration camp; holocaust; illness; interned people; patient; health care